LncRNA LINC00958 Activates mTORC1/P70S6K Signalling Pathway to Promote Epithelial-Mesenchymal Transition Process in the Hepatocellular Carcinoma. (9th August 2021) - Lan, Chuangxia; Wang, Yanming; Su, Xiaofei; Lu, Jing; Ma, Saisai
Abstract: The study aimed to investigate the influence of LINC00958 on the EMT process of hepatocellular carcinoma (HCC). In our study, The LINC00958 was up-regulated in HCC tissues and cell lines. LINC00958 silencing inhibited cell proliferation, migration, and EMT process of HCC. The analysis of TCGA and StarBase showed that NUDT19 was a direct target of LINC00958 and was positively regulated by LINC00958. Besides, NUDT19 activated mTORC1/P70S6K signalling pathway. Both NUDT19 overexpression and mTORC1 activator MYH1485 reversed the inhibitory effect of LINC00958 silencing on proliferation, migration, and EMT process of HCC. In conclusion, LINC00958 silencing inhibited the proliferation, migration, and EMT process of HCC via inhibiting NUDT19 mediated mTORC1/P70S6K signalling pathway.